Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5194/acp-22-3379-2022
|View full text |Cite
|
Sign up to set email alerts
|

Lightning activity in northern Europe during a stormy winter: disruptions of weather patterns originating in global climate phenomena

Abstract: Abstract. In this study, we use World Wide Lightning Location Network data and investigate properties of more than 90 000 lightning strokes which hit northern Europe during an unusually stormy winter in 2014/15. Thunderstorm days with at least two strokes hitting an area of 0.5∘ × 0.5∘ occurred 5–13 times per month in the stormiest regions. Such frequency of thunderstorm days is about 5 times higher than the mean annual number calculated for the same region over winter months in 2008–2017. The number of indivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The constant ratio is calculated using two factors: the number of strokes per flash (flash multiplicity) and the mean ratio of IC to CG flashes (also known as the Z ratio) in the high latitudes. The flash multiplicity is highly sensitive to both the detection efficiency and the algorithm used to group strokes into flashes. The mean multiplicity value for high-latitude studies is estimated to be 1.2 . In addition, the mean Z ratio of high-latitude flashes is between 1 and 1.3. To evaluate the sensitivity of the constant ratio, we have used different values (1:2 and 2:1) in Table S4 to assess the uncertainty of estimated LNO x emissions.…”
Section: Methodsmentioning
confidence: 99%
“…The constant ratio is calculated using two factors: the number of strokes per flash (flash multiplicity) and the mean ratio of IC to CG flashes (also known as the Z ratio) in the high latitudes. The flash multiplicity is highly sensitive to both the detection efficiency and the algorithm used to group strokes into flashes. The mean multiplicity value for high-latitude studies is estimated to be 1.2 . In addition, the mean Z ratio of high-latitude flashes is between 1 and 1.3. To evaluate the sensitivity of the constant ratio, we have used different values (1:2 and 2:1) in Table S4 to assess the uncertainty of estimated LNO x emissions.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the correlation between lightning and rainfall was weak during the dry season, as shown in Figure 6(b). Various studies have shown that the factors that influence lightning-rainfall are: type of thunderstorm, geographic region, local climatology, and convection regime [5], [10], [11], [15]. In general, the lightning-rainfall characteristics in Padang follow the pattern of region B, where region B has two rainfall peaks, namely March-April-May (MAM) and October-November (ON).…”
Section: Rainfallmentioning
confidence: 99%
“…Using optical strokes data detected by Vela satellite in [5], the author identifies the strokes optical energy that is 100 times more powerful than usual lightning and discovered 20 strokes in the super-bolts category. In [6], the authors depict lightning activity across northern Europe during a severe winter in 2008-2017. During the colder months (Dec, Jan and Feb), the mean energy of recorded strokes was two orders of magnitude bigger than the global mean stroke energy of 1 kJ.…”
Section: Introductionmentioning
confidence: 99%